Short distribution channels of horticulture produce in Open-air markets in the City of Iporá-GO, Brasil (Research, Society and Development, 2020)
The short distribution channel main characteristics are the interaction between actors within the scope of value chains, the reduction of intermediaries’ agents, the product valuation, and, in addition to all of this, the promotion of the local culture. In the city of Iporá-Go, the open-air markets play an important role in the economic and social development of the region, by using short distribution channels. Within this perspective, the following article aims to present the socioeconomic diagnosis of stallholders who are part of these distribution channels. The methodologies used for the analysis on Iporá’s open-air markets case study were both qualitative and quantitative. The primary data survey was carried out through forms and questionnaires that 35 stallholders filled out and answered, from April to June of 2019.  The research is identified, regarding its objectives, as descriptive and exploratory. Analyzing the results, it can be observed that 41.75% of the stallholders produce the food they sell at the open-air markets; 42.85% of the total make an amount of money that is above four minimum wages; when it comes to the education level, 31.42% of the interviewees have finished elementary school. The approach of these themes allows the understanding of the conjuncture in which the actors that participate in these short distribution channels in Iporá-GO are inserted, as well as their capillarity in the development of the region.